Increased systemic microbial translocation is associated with depression during early pregnancy. (February 2018) - Zhou, Zejun; Guille, Constance; Ogunrinde, Elizabeth; Liu, Renyu; Luo, Zhenwu; Powell, Anna; Jiang, Wei
Abstract: Plasma level of microbial translocation is a marker of mucosal permeability. Increased mucosal permeability ignites elevated microbial translocation and as a consequence of systemic inflammation. Pregnant women with depression have higher levels of inflammatory markers relative to pregnant women without depression, however, no studies have reported whether systemic microbial translocation will change in depressed women during pregnancy. In this study, we examined the plasma LPS level of depressed women during pregnancy. The results showed that the plasma LPS level was significantly increased in depressed mothers during their 8–12 weeks gestation compared to healthy controls. Compared to 8–12 weeks gestation, the plasma LPS levels were significantly decreased at 24–28 weeks gestation and 6–8 weeks postpartum in both depressed subjects and healthy controls. Furthermore, the plasma levels of pro-inflammatory cytokines (TNF-α and MCP/CCL2) associated with microbial translocation were significantly increased in depressed subjects during 8–12 weeks gestation compared to healthy controls. These results indicate that the level of microbial translocation is increased in depressed women during early pregnancy.